Rancang bangun pendeteksi suhu dan gas amonia dengan metode fuzzy logic pada kandang ayam broiler berbasis iot - Setiawati, Dhea; Risky Via Yuliantari; Bagus Fatkhurrozi (Politeknik Negeri Batam, 2025)
Temperature, humidity, and ammonia gas are critical factors that affect the health and productivity of broiler chickens. Manual monitoring commonly carried out by farmers is inefficient and prone to errors, thus requiring an automatic system capable of real-time detection. This study developed a monitoring system for temperature, humidity, and ammonia levels in broiler chicken coops based on the IoT using the Sugeno fuzzy logic method. The system was designed with a NodeMCU ESP8266 microcontroller integrated with a DHT22 sensor for temperature and humidity, and a MQ-135 sensor for ammonia gas. Measurement data are displayed in real time through an LCD, Blynk application, and ThingSpeak allowing remote monitoring. The decision-making process is carried out using Sugeno fuzzy logic to classify coop conditions into safe, alert, or danger. Experimental results show MAPE values of 2,7% for temperature and 3,5% for humidity. The system operated continuously for 14 days and generated 1,265 consistent monitoring data points. Thus, the proposed system assists in automatic coop monitoring and supports increased broiler chicken productivity.